2023
DOI: 10.4094/chnr.2023.29.1.84
|View full text |Cite
|
Sign up to set email alerts
|

Health-related quality of life in children with epilepsy: a concept analysis

Abstract: Purpose: This study aimed to conduct a concept analysis of health-related quality of life in children with epilepsy to promote conceptual clarification and facilitate mutual understanding of the concept. Methods: Walker and Avant's concept analysis method was adopted.Results: Health-related quality of life in children with epilepsy consists of six attributes: health status, inner strength, close relationships, resource-rich community, social acceptance, and changeability. According to the ecological system par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 49 publications
1
0
0
Order By: Relevance
“…Some studies have explored the correlation between health-related quality of life (HRQoL) and clinical characteristics in children with epilepsy. A study found a negative correlation between HRQoL scores and seizure frequency in children with epilepsy, which is consistent with the present study's findings that there was no significant correlation between HRQoL and frequency of fits in the monotherapy group (17).…”
Section: Discussionsupporting
confidence: 93%
“…Some studies have explored the correlation between health-related quality of life (HRQoL) and clinical characteristics in children with epilepsy. A study found a negative correlation between HRQoL scores and seizure frequency in children with epilepsy, which is consistent with the present study's findings that there was no significant correlation between HRQoL and frequency of fits in the monotherapy group (17).…”
Section: Discussionsupporting
confidence: 93%